2012
DOI: 10.1007/s00011-011-0417-3
|View full text |Cite
|
Sign up to set email alerts
|

FOXO1 involvement in insulin resistance-related pro-inflammatory cytokine production in hepatocytes

Abstract: FOXO1 potentiates pro-inflammatory cytokine production in insulin-resistant hepatocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 45 publications
(62 reference statements)
3
22
0
Order By: Relevance
“…This observation is even more surprising as dexamethasone increased the expression of Foxo1, confirming a previous study with INS-1 cells showing that dexamethasone increases, while prolactin decreases, the transcript levels of Foxo1 [27]. Increased protein levels in combination with reduced phosphorylation and activation of FOXO1 after dexamethasone exposure has been described in a variety of cells, including hepatocytes, cardiomyocytes and tenocytes [28][29][30]. Interestingly, in tenocytes, dexamethasone-mediated inhibition of FOXO1 phosphorylation was counteracted by insulin.…”
Section: Discussionsupporting
confidence: 83%
“…This observation is even more surprising as dexamethasone increased the expression of Foxo1, confirming a previous study with INS-1 cells showing that dexamethasone increases, while prolactin decreases, the transcript levels of Foxo1 [27]. Increased protein levels in combination with reduced phosphorylation and activation of FOXO1 after dexamethasone exposure has been described in a variety of cells, including hepatocytes, cardiomyocytes and tenocytes [28][29][30]. Interestingly, in tenocytes, dexamethasone-mediated inhibition of FOXO1 phosphorylation was counteracted by insulin.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, the induction of active chromatin states by FOXO1 has been described in a previous study (18). Insulin has the ability to negatively regulate the expression and transcriptional activity of FOXO1 (24,25). FOXO1 has been reported to confer an inhibitory effect of insulin on gene transcription through binding to the IRE in the promoter sequences of target genes (26).…”
Section: Discussionmentioning
confidence: 82%
“…We demonstrated that CGI-58 deficiency-induced IL-1β transcription via activating a transcriptional factor forkhead box-containing protein O subfamily-1 (FOXO1) [9] , which was previously reported to involve in multiple proinflammatory cytokine production in hepatocytes, adipocytes and macrophages by us [10][11] and others [12][13][14] . In further studies, we verified that CGI-58/inflammasome pathway-mediated IL-1β secretion stimulates the expression of suppressor of cytokine signaling 3 (SOCS3), which dampens insulin signaling in macrophages [9] .…”
Section: Research Highlightmentioning
confidence: 81%
“…In further studies, we verified that CGI-58/inflammasome pathway-mediated IL-1β secretion stimulates the expression of suppressor of cytokine signaling 3 (SOCS3), which dampens insulin signaling in macrophages [9] . The impaired insulin signaling activates FOXO1 activity by decreasing FOXO1 phosphorylation [9][10][11] . Thus, CGI-58 deficiency activates NLRP3-inflammasome pathway to initiate a vicious cycle (IL-1β -SOCS3 -FOXO1 -IL-1β) (Figure 1).…”
Section: Research Highlightmentioning
confidence: 99%